Digital competences in Poland in light of European Union “DESI” Reports - Ewa MATUSKA; Joanna GRUBICKA (Communications of International Proceedings, 2022)
The article is dedicated to the meaning of digital competences development on the example of European Union policy and its measures. It is consisted with two parts: theoretical one, based on literature review, digital competences scope evolution in EU legislative documents and programs  and with the empirical part presenting a comparative  analysis  of digital competences status quo in Poland based on DESI reports from 2021, 2020 and 2019. In discussion are assumed gaps in area of human capital and digitals skills development in case of Poland. In conclusions is stressed the importance of digital competences for sustainable development of society and economy 4.0 and for human resources management with aspects of cybersecurity.
Keywords: Digital Competences; EU Digital Strategy; Human Capital; Cybersecurity